Effect of post-shooting foliar spray of fertilizes on yield and economics of banana (Musa paradisiaca) cv. Grand Nain (Current Horticulture, 2024)
The experiment was conducted to find out the effect of post-shooting foliar spray of fertilizers on yield and economics of banana (Musa paradisiaca L.) cv. Grand Nain during 2012-13 at Regional Horticultural Research Station, ASPEE College of Horticulture and Forestry, Navsari Agricultural University, Navsari (Gujarat). The experiment was laid out with 11 treatments in a randomized block design with three replications. The treatments included SOP (1.0%, 1.5% and 2.0%), urea (1.0%, 1.5% and 2.0%), KNO3 (0.5%, 1.0% and 1.5%) and pouch feeding (300g fresh cowdung + 20g ammonium sulphate + 10g SOP) along with the control. The first spray was done immediately after complete emergence of bunch while the second was done 15 days after first spray. All bunches were covered with 18 µ blue polythene. Quantity parameters were recorded and analyzed statistically. The minimum days taken from flowering to harvesting and maximum length of bunch, girth of bunch, weight of third hand, length of finger, girth of finger, weight of bunch and yield were significant in SOP (1.5%). The bunches sprayed twice with SOP (1.5%) and sleeve with 18µ blue polythene were most remunerative since they gave highest gross income and net return with maximum benefit cost ratio.
Keywords: Post-shooting; Foliar spraying; Yield; Sleeving; Pouch feeding; SOP; Urea; KNO3